Dioxins and furans in air and deposition: A review of levels, behaviour and processes - Lohmann, Rainer; Jones, Kevin C. (The Science of the total environment, 1998)
This paper is a comprehensive, critical review of the levels, behaviour and processes affecting polychlorinated dibenzo- p-dioxins and -furans (PCDD/Fs) in air and deposition. Aspects of sampling, analysis and quality assurance/control are discussed initially, before a review of the PCDD/F concentrations in ambient air is presented. The general trend in ΣP 4–8CDD/F (and ΣTEQ) is: remote sites<0.5 pg/m 3 (ΣTEQ<10 fg/m 3); rural sites∼0.5–4 pg/m 3 (ΣTEQ∼20–50 fg/m 3); and urban/industrial sites∼10–100 pg/m 3 (ΣTEQ∼100–400 fg/m 3). The commonly held view that a consistent mixture of PCDD/Fs in air exists is evaluated and questioned. Issues of seasonality and short-term changes in air concentrations are also critically discussed, with respect to the possibility of seasonal emission sources to air and seasonally dependent loss processes. Data on the gas–particle partitioning of PCDD/Fs in air are reviewed; the limited database to date is believed to provide evidence for an exchangeable transfer of PCDD/Fs between these two phases. The potential importance of photolytic and radical reaction degradation processes and wet/dry deposition processes in modifying the mixture of PCDD/Fs in air is discussed. Some homologue/congener specific `weathering' of the mixture of PCDD/Fs emitted to the atmosphere clearly occurs, but in general PCDD/Fs have `long' atmospheric residence times, rendering them subject to long-range atmospheric transport. Data are reviewed which relate the mixture of PCDD/Fs in air to that in deposition; this leads to the conclusion that different homologue groups (which are partitioned differently between the gas and particulate phase) are transferred to the earth's surface with broadly similar efficiencies.